2013
DOI: 10.1074/mcp.m112.023754
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Mass Spectrometry-based Analysis of the Fission Yeast Proteome

Abstract: We report a high quality and system-wide proteome catalogue covering 71% (3,542 proteins) of the predicted genes of fission yeast, Schizosaccharomyces pombe, presenting the largest protein dataset to date for this important model organism. We obtained this high proteome and peptide (11.4 peptides/protein) coverage by a combination of extensive sample fractionation, high resolution Orbitrap mass spectrometry, and combined database searching using the iProphet software as part of the Trans-Proteomics Pipeline. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 57 publications
5
24
1
Order By: Relevance
“…The 3753 proteins identified in our study represent 74% of the predicted fission yeast proteins, making it one of the most comprehensive published protein datasets of this organism to date. To enable triple-SILAC labeling and avoid quantification problems arising from arginine to proline conversion (38), we exclusively used SILAC labeling with lysine and digestion with endoproteinase Lys-C. Our data complement the recently published PeptideAtlas of the fission yeast proteome obtained using trypsin (19), and it increases the coverage of the S. pombe proteome from 3542 to a total of 4068 proteins.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The 3753 proteins identified in our study represent 74% of the predicted fission yeast proteins, making it one of the most comprehensive published protein datasets of this organism to date. To enable triple-SILAC labeling and avoid quantification problems arising from arginine to proline conversion (38), we exclusively used SILAC labeling with lysine and digestion with endoproteinase Lys-C. Our data complement the recently published PeptideAtlas of the fission yeast proteome obtained using trypsin (19), and it increases the coverage of the S. pombe proteome from 3542 to a total of 4068 proteins.…”
Section: Discussionmentioning
confidence: 70%
“…We compared our absolute quantification to several studies that used different technologies to derive absolute protein amounts in S. pombe as follows: MS intensity-based absolute quantification (18,19,22) and fluorescence microscopybased quantitation (27,43). It has been reported that …”
Section: Functional Classes Of Fluctuating Proteins and Phosphorylatimentioning
confidence: 99%
See 1 more Smart Citation
“…Although the genome of the cyanobacterium S. elongatus is not as extensive as that in mammalian systems, this percentage is still impressive, especially when compared with the 60% to 70% reported for other, smaller genomes such as yeast (52).…”
Section: Discussionmentioning
confidence: 89%
“…The presence of 10 ATG triplets in the interval between the prt2 start site and the annotated ATG of the putative SPBC8E4.02c ORF is consistent with prt2 being a lncRNA rather than an mRNA. In support of this conclusion, deep analyses by mass spectrometry of the protein contents of the fission yeast cell have failed to detect any peptides derived from the putative SPBC8E4.02c ORF (12,13), while readily detecting the Pho84 polypeptide at a level of ~12,000 molecules per cell (13).…”
Section: Resultsmentioning
confidence: 98%